Approach bias modification training in bulimia nervosa and binge-eating disorder: a pilot randomized controlled trial - Brockmeyer, Timo; Friederich, Hans-Christoph (The international journal of eating disorders, 2019)
Objective Bulimia nervosa (BN) and binge-eating disorder (BED) are associated with poorly controlled approach behavior toward food resulting in binge eating. Approach bias modification (ABM) may reduce these automatic action tendencies (i.e., approach bias) toward food and may thus decrease binge eating and related symptoms. Method A total of 56 patients with BN/BED participated in this double-blind, randomized controlled trial (RCT) comparing real and sham ABM. The real ABM condition adopted an implicit learning paradigm in which participants were trained to show avoidance behavior in response to food cues. Participants in the sham condition used a similar task but were not trained to avoid food cues. Both conditions comprised 10 training sessions within 4 weeks. Results Participants in both groups experienced significant reductions in binge eating, eating disorder symptoms, trait food craving, and food cue reactivity. Real ABM tended to result in greater reductions in eating disorder symptoms than sham ABM. Food intake, approach bias, and attention bias toward food did not change. Discussion This is the first RCT on ABM in eating disorders. The findings provide limited support for the efficacy of ABM in BN/BED and pose questions regarding its active ingredients and its usefulness as a stand-alone treatment for eating disorders.
Gesehen am 27.03.2020